2017
DOI: 10.1902/jop.2017.170286
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic Response to Periodontal Therapy and Multivariable Prediction of Clinical Outcome

Abstract: Long-term microbiologic outcomes of periodontal therapy with adjunctive antibiotics either in T1 or T2 were similar. Detection of Pm before therapy was a predictor for persistence of sites with PD >4 mm and BOP at 12 months post-treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 46 publications
1
20
1
3
Order By: Relevance
“…The organism is recognized as a member of the human periodontitis core microbiome [ 1 ], and is included in the orange complex cluster group of subgingival bacteria significantly associated with deep periodontal pockets [ 5 ]. Pre-treatment presence of subgingival P. micra in periodontitis patients is a significant predictor of post-treatment persistence of residual ≥5 mm periodontal pockets that bleed on probing [ 6 ]. Additionally, elevated subgingival levels of P. micra remaining after conventional mechanical-surgical treatment of severe periodontitis patients predisposes them to a significantly increased risk of further periodontal breakdown [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The organism is recognized as a member of the human periodontitis core microbiome [ 1 ], and is included in the orange complex cluster group of subgingival bacteria significantly associated with deep periodontal pockets [ 5 ]. Pre-treatment presence of subgingival P. micra in periodontitis patients is a significant predictor of post-treatment persistence of residual ≥5 mm periodontal pockets that bleed on probing [ 6 ]. Additionally, elevated subgingival levels of P. micra remaining after conventional mechanical-surgical treatment of severe periodontitis patients predisposes them to a significantly increased risk of further periodontal breakdown [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…P. micra is often poorly removed from periodontitis sites with conventional forms of periodontal therapy, such as repeated root surface debridement, periodontal access flap surgery, systematic maintenance care, and meticulous supragingival plaque control [ 6 , 7 , 8 , 9 , 12 ]. This may be due to marked adherence of P. micra to gingival crevicular epithelium [ 13 ], which is less likely to be affected by periodontal root instrumentation than tooth-associated microbial biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is effective against anaerobes such as P. gingivalis and P. intermedia [ 24 ]. Studies have suggested that Metronidazole combined with Amoxicillin or Amoxicillin–Clavulanate potassium, it may be with great impact in the management of patients with aggressive periodontitis [ 23 ] [ 25 ] [ 26 ] [ 27 ] [ 28 ]. In our study, Metronidazole was mostly used in combination with Amoxicillin 12.1% and with Spiramycin in 10.2%.…”
Section: Discussionmentioning
confidence: 99%
“…Critics point out that it is not a requirement for proper treatment and patients benefited from antibiotics irrespective of the knowledge of the bacterial status. [4][5][6] Especially the fact of being A. actinomycetemcomitans-positive or -negative did not change the effect of the antibiotics. 4 Proponents invoke that tests are a useful tool in finding the optimal and individualized treatment option to patients, in particular, when used on patients with (former classified) severe chronic or aggressive periodontitis who do not respond favorably to conventional mechanical therapy.…”
Section: Introductionmentioning
confidence: 88%